Principles of generative phonology : an introduction - Jensen, John T. (John Tillotson) (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2004)
Principles of Generative Phonology is a basic, thorough introduction to phonological theory and practice. It aims to provide a firm foundation in the theory of distinctive features, phonological rules and rule ordering, which is essential to be able to appreciate recent developments and discussions in phonological theory. Chapter 1 is a review of phonetics; chapter 2 discusses contrast and distribution, with emphasis on rules as the mechanism for describing distributions; chapter 3 introduces distinctive features, natural classes, and redundancy; chapter 4 builds on the concept of rules and sho.